Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6fo00979d
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional extract from corn steep liquor: antioxidant and surfactant activities

Abstract: In the last few years the awareness of consumers and institutions about the impact that our industrial processes has on health and the environment has increased, demanding more natural products. In this work, a multifunctional bioactive extract with surfactant and antioxidant properties, composed mainly of C16 and C18 fatty acids, and phenolic compounds (vanillic acid, p-coumaric acid, ferulic acid, sinapic acid and quercetin) was obtained from corn steep liquor (CSL). Different liquid-liquid extraction protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 20 publications
(24 reference statements)
4
46
0
1
Order By: Relevance
“…as palmitic, stearic, oleic, and linolelaidic acids, which represented 2 %, 7 %, 12 % and 22 % of the biosurfactant extract, respectively. These results confirm that this extract has a significant lipophilic character, as seen previously [33,38]. As a result of the lipidic nature of this biosurfactant, it is proposed that it could improve the permeation of drugs through the skin.…”
Section: Characterisation Of Biosurfactant Extractsupporting
confidence: 86%
“…as palmitic, stearic, oleic, and linolelaidic acids, which represented 2 %, 7 %, 12 % and 22 % of the biosurfactant extract, respectively. These results confirm that this extract has a significant lipophilic character, as seen previously [33,38]. As a result of the lipidic nature of this biosurfactant, it is proposed that it could improve the permeation of drugs through the skin.…”
Section: Characterisation Of Biosurfactant Extractsupporting
confidence: 86%
“…In previous studies it has been demonstrated the presence of biosurfactants in CSW (Rodríguez-López et al, 2016;Vecino et al, 2014Vecino et al, , 2015a. This industrial stream is characterized by a high viscosity (it contains 50% of solids), low concentration of sugars and high concentration of lactic acid, which has been employed by many researchers as nutritional supplement in the production of microbial metabolites (Guerra-Rodríguez & Vázquez, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the composition of the biosurfactant extracted from CSW, it was characterized as a lipopeptide, composed by C16 and C18 fatty acids, comprising oleic, linoleic and stearic fatty acids which are linked to a small fraction of an organic nitrogen chain composed by amino acids (Rincón-Fontan, Rodríguez-López, Rodríguez-López, Vecino, Barbosa-Pereira, Moldes, & Cruz, 2016;Vecino, Rodríguez-López, Cruz, & Moldes, 2015b). Therefore, Rincón-Fontán et al (2017) reported that this biosurfactant possesses a molecular weight similar to the lipopeptides produced by B.subtillis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fatty acids profile of the biosurfactant extracts was analyzed by GC-MS-MS (gas chromatography coupled to a mass spectrometer) on a Model Scion 451 GC (Bruker) equipped with a PTV 1019 universal capillary injector, coupled to a mass spectrometer, controlled by System Control software. Prior to analysis, the biosurfactant extracts were submitted to a derivatization process following the procedure described by Rodríguez-López et al [36]. Afterwards, 1 mL of sample was injected using a splitless mode.…”
Section: C) Fatty Acid Composition Determined By Gc-ms-msmentioning
confidence: 99%